Disk-Integrated Lunar Brightness Temperatures between 89 and 190 GHz - Martin J. Burgdorf; Stefan A. Buehler; Imke Hans; Marc Prange (Advances in Astronomy)
Measurements of the disk-integrated brightness temperature of the Moon at 89, 157, 183, and 190 GHz are presented for phase angles between -80° and 50° relative to full Moon. They were obtained with the Microwave Humidity Sounder (MHS) on NOAA-18 from 39 instances when the Moon appeared in the deep space view of the instrument. Polynomials were fitted to the measured values and the maximum temperature and the phase angle of its occurrence were determined. A comparison of these results with the predictions from three different models or rather parametrical expressions by Keihm, Mo & Kigawa, and Yang et al. revealed significantly larger phase lags for the lower frequencies in the measurements with MHS. As the Moon has appeared thousands of times in the field of view of all microwave sounders combined, this investigation demonstrates the potential of weather satellites for fine tuning models and establishing the Moon as extremely accurate calibration reference.